2007
DOI: 10.1007/s00181-007-0143-4
|View full text |Cite
|
Sign up to set email alerts
|

Gender wage gap studies: consistency and decomposition

Abstract: Abstract:This paper reviews the empirical literature on the gender wage gap, with particular attention given to the identification of the key parameters in human capital wage regression models. This is of great importance in the literature for two main reasons. First, the main explanatory variables in the wage model, i.e., measures of work experience and the time-out-of-work, are endogenous. As a result, applying traditional estimators may lead to inconsistent parameter estimates. Second, empirical evidence on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 39 publications
(54 reference statements)
1
73
0
8
Order By: Relevance
“…A variety of national and international studies on the gender-specific wage differential (gender pay gap) shows a wage disadvantage for women Blau/Kahn 2006Federal Ministry of Family Affairs, Senior Citizens, Women and Youth 2008a, b;European Commission 2007; for an overview, see Kunze 2008). Only a few articles are related to the gender pay gap in leadership positions and attempt to explain them (Bertrand/Hallock 2001;Kirchmeyer 2002;Lausten 2001).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of national and international studies on the gender-specific wage differential (gender pay gap) shows a wage disadvantage for women Blau/Kahn 2006Federal Ministry of Family Affairs, Senior Citizens, Women and Youth 2008a, b;European Commission 2007; for an overview, see Kunze 2008). Only a few articles are related to the gender pay gap in leadership positions and attempt to explain them (Bertrand/Hallock 2001;Kirchmeyer 2002;Lausten 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This proxy has been criticised on the grounds that people do not work continuously after having completed school, and this is particularly true in South Africa (Woolard, 2002). A further issue with this proxy relates to the fact that women often have more interrupted work histories than their male counterparts due, for example, to family responsibilities (see for instance, Kunze, 2008). Thus, if work experience itself is gendered, then the implication is that a measured gender earnings gap with such a proxy may be overestimated (or biased upwards).…”
Section: Explanatory Variables and The Gender Earnings Gap: Some Concmentioning
confidence: 99%
“…It is in fact observed that men and women move into different fields, in other words there is a degree of self-selection into occupations groups (Kunze, 2008). The theory of compensating differentials, for instance, argues that women may choose occupations or jobs that fit in with their lifestyles, more specifically, as far as family responsibilities and child care is concerned.…”
Section: Explanatory Variables and The Gender Earnings Gap: Some Concmentioning
confidence: 99%
See 1 more Smart Citation
“…Keeping in mind the well-documented gender pay gap (Holst and Busch, 2010;Blau and Kahn, 2006;Kunze, 2008), it is clear that women will often have less bargaining power than their spouses. Moreover, men will then expect fewer returns from the market.…”
Section: Bargaining Power and Support Gapmentioning
confidence: 99%